USE OF PLASTICIZERS IN POLYMERS - Sabirova Diloram Kabulovna; Ergasheva Hikoyat Turapovna; Niyazova Gulkhayo Parpievna (International Journal of Innovations in Engineering Research and Technology, 2023)
This article explores the role of plasticizers in polymers, elucidating their significance in enhancing flexibility and mechanical properties. The study encompasses a thorough literature analysis, presenting various plasticizer types, their mechanisms, and the influence on polymer structures. The research employs diverse methods to investigate the effects of plasticizers on polymer materials, leading to comprehensive results. The discussion section delves into the implications of the findings, providing insights into potential applications and future research avenues. Conclusively, the article offers valuable suggestions for optimizing polymer formulations to achieve desired properties through plasticizer incorporation.